(untitled) (Revista Española de Fisiología, 1996)
The rat tail artery during a 180 min incubation period in a medium containing glucose plus oxfcnicine (an inhibitor of fatty acid oxidation) did not show changes in the contractile responses to adrenaline. In a substrate-free medium the extent of the contractions underwent a slight decrease during the last 60 min of incubation. When the substrate-free medium contained 2-deoxyglucose (an inhibitor of glycolysis and glycogenolysis) or oxfcnicine, the decline of the contractile activity developed faster and attained a similar extent with each inhibitor. When the substrate-free medium contained 2-deoxyglucose together with oxfenicine or methylpalmoxirate (an inhibitor of fatty acid oxidation) the arteries displayed a pronounced and early fall in the contraction strength. These data suggest that in the presence of glucose the reserve substrates are not necessary as fuel source for the arterial contractions. However, in substrate-free conditions they constitute an important energy source. Furthermore, glycogen and triacylglyccrol share the supply of energy and there does not seem to be any other reserve material in the smooth muscle of the rat tail artery.